TINJAUAN PENGENDALIAN HAMA TIKUS PADA TANAMAN PADI MA’HAD AL-ZAYTUN PERSPEKTIF UNDANG-UNDANG NOMOR 32 TAHUN 2024 DAN MAQASHID SYARIAH - Sodikin, Ali; Rohmah, Siti Ngainnur; Sajali, Munawir (Gapenas Publisher, 2025)
Food is a basic need and a human right essential for national stability. Rice, as the primary source, plays a strategic role in Indonesia's food security. Rice production declined in 2021 due to land degradation, climate change, and pest attacks, particularly the rice field rat, which is the most destructive pest. This study evaluates ecologically based rat pest control in accordance with Law No. 32 of 2024 and the principles of maqashid sharia at Ma'had Al-Zaytun, which implements sustainable agriculture, to provide effective recommendations for increasing rice productivity and preserving the ecosystem. The purpose of this study is to examine rat pest control in rice fields at Ma'had Al-Zaytun from the perspective of Law No. 32 of 2024 and Maqashid Sharia. This research uses a normative legal approach or literature study. The data used include primary sources: Law No. 32 of 2024, the book